HUBUNGAN ANTARA GAYA MENGAJAR GURU DENGAN INTERAKSI SOSIAL TERHADAP PRESTASI BELAJAR PELAJARAN MATEMATIKA DI SMK PGRI 1 SURAKARTA - Ningsih, Nur Wigati (TALENTA, 2015)
This research purpose to knowing the relation between teacher styles teach with students  social  interaction  and  also  teacher  styles  teach  with  achievement  learn  and social interaction with students achievement learn in accepting mathematics lesson.Measuring  instrument  used  by  teacher  style  teaches  scale,  social  interaction scale  and  also  use  the  achievement  learn  mathematics  value.  Population  is  student  of PGRI  I  Vocational  High  School  of  Surakarta  summed  apply  sample  of  counted  60 students, is obtained through the technique of purposive random sampling. The dataanalyze  method  used  analyze  Product  Moment  from  Pearson  technique  with constructively SPSS for Windows Release 21.0.Result of data analysis indicate that there is positive  relation which significant between teacher style teach with the achievement learn, shown by a correlation value (r) equal  to  0,468;  p  =  0,002  (p<0,05)  meaning  progressively  style  goodness  teach  the teacher of hence good progressively also achievement learn  the student, so also on the contrary  bad  progressively  style  teach  the  teacher  of  hence  bad  progressively  also achievement  learn  the  student.  Analyze  hereinafter  interaction  social  with  the achievement  learn  the  student  obtained  a  correlation  coefficient  value  (r)  0,524;  p  = 0,001 (p<0,05), its meaning progressively social interaction goodness learn hence good progressively  also  achievement  learn  the  student,  so  also  on  the  contrary  bad progressively  social  interaction  learn  hence  bad  progressively  also  achievement  learn student.Key word: Achievement Learn, Teacher Style Teach, Students